2016
DOI: 10.1111/echo.13364
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid annular plane systolic excursion in chronic thromboembolic pulmonary hypertension before and after pulmonary thromboendarterectomy

Abstract: In patients with CTEPH, TAPSE paradoxically decreased by 50% early after PTE. TAPSE correlated inversely with PVR prior to PTE, but this correlation was lost completely after PTE. Thus, despite the immediate and marked decrease in afterload postoperatively, TAPSE did not improve; thus, TAPSE cannot be used as an early marker for surgical success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
5
11
0
Order By: Relevance
“…Our previous study has confirmed this 8 . In addition, our experience and some studies have shown that RV myocardial motion in the basal segment did not improve early after pulmonary thromboendarterectomy in patients with chronic thromboembolic PH 9,10 . We hypothesize that regional RV myocardial motion, especially the motion in the mid segment, may reflect the RV systolic function more accurately than the global RV longitudinal strain.…”
Section: Introductionsupporting
confidence: 65%
“…Our previous study has confirmed this 8 . In addition, our experience and some studies have shown that RV myocardial motion in the basal segment did not improve early after pulmonary thromboendarterectomy in patients with chronic thromboembolic PH 9,10 . We hypothesize that regional RV myocardial motion, especially the motion in the mid segment, may reflect the RV systolic function more accurately than the global RV longitudinal strain.…”
Section: Introductionsupporting
confidence: 65%
“…Using transthoracic echocardiography, it is noted that although TAPSE correlates inversely pre-PTE, the correlation is lost completely post-PTE such that TAPSE cannot be used as an early marker for successful surgery. 6 When evaluating additional markers of longitudinal contraction, similar results were observed for S' and basal RV free wall strain correlating well with PVR preoperatively, but the association falls apart after bypass. 7,8 However, with a more global evaluation of RV function, the right-sided index of myocardial performance (RIMP, or right Tei index), is used the correlation holds both before and after successful pulmonary thromboendarterectomy.…”
supporting
confidence: 63%
“…In the assessment of cardiac function post pulmonary endarterectomy, TAPSE demonstrated significant worsening despite improvement in PVR. 25 In this setting, it was highlighted that the rocking motion of the heart contributed to TAPSE measurement, and this rocking motion was lost following pulmonary endarterectomy, hence the reduction in value. Another study looked at pseudo-normalized TAPSE in a group with RV dysfunction.…”
Section: Right Ventricular Function By Echocardiographymentioning
confidence: 99%